Boon or bane? : The role of filial piety, relationship quality, caregiver gender on work-family interface among working caregivers of the elderly - Leong, Anthony Xueheng (Nanyang Technological University, 2021)
The present study advances the existing knowledge on the work-family interface among working caregivers of the elderly with new ideas about filial piety, relationship quality and gender. I examined the two dimensions of filial piety, compassionate reverence (CR) and pragmatic obligation (PO), and their effects on work-family interface; CR was hypothesized to lead optimal work-family experiences (less work-family conflict (WFC) and more work-family-enrichment (WFE)), while PO was predicted to lead more WFC and less WFE. I investigated whether higher levels of CR weakens the negative relationship between WFC and vitality, and if it strengthens the positive relationship between WFE and vitality. I also explored if higher levels of PO strengthens the negative relationship between WFC and vitality, and if it weakens the positive relationship between WFC and vitality. A three-way interaction between relationship quality (closeness to care recipient; CCR), CR and work-family interface in predicting caregiver wellbeing (vitality) was also studied. Finally, gender was considered in a three-way interaction between PO and work-family interface in predicting caregiver wellbeing (vitality). Full-time workers who take care of an older relative were recruited; 195 participants (143 women, 52 men) were recruited. Participants completed an initial survey followed by three daily surveys over five consecutive working days. Data were analysed using multi-level modelling. The results suggest that the two dimensions of filial piety have unique relationship with work-family interface; CR was positively associated with Family-Enriches-Work (FEW) and Work-Enriches-Family (WEF), while PO was negatively associated with WEF and Family-Interference-with-Work (FIW). The negative relationship between Work-Interference-with-Family (WIF) and vitality was more pronounced among caregivers who perceive higher PO than those who perceive lower PO. When FIW was experienced, caregivers higher in CR and CCR reported lower vitality than those with lower or an average level of CCR. When FEW was experienced, caregivers higher in CR and CCR reported higher bedtime vitality than any other combination of CR and CCR. At higher levels of PO and FIW (or PO and WEF), women caregivers experienced more vitality than men caregivers. At higher levels of PO and FEW, men caregivers experience more vitality than women caregivers. This is the first study to examine the relationship between the multi-dimensional filial piety and the work-family interface among working caregivers of the elderly, with considerations of relationship quality and gender. Findings point to potential directions for future research and offer suggestions on how to aid working caregivers to optimize interactions between work and family domains. Keywords: Work-family interface, family-interference-with-work, work-interference-with-family, work-enriches-family, family-enriches-work, filial piety, gender, relationship quality, closeness to care recipient, multilevel modelling, factor analysis